Brockarchaeota, a novel archaeal phylum with unique and versatile carbon cycling pathways - Valerie De Anda (Nature Portfolio, 2021)
Geothermal environments are hotspots for carbon cycling. Here, De Anda et al. reconstruct archaeal genomes from terrestrial and deep-sea geothermal sediments, and propose the classification of these microbes as a new phylum, ‘Brockarchaeota’, with unique metabolic capabilities including non-methanogenic anaerobic methylotrophy.